Expanding armamentarium in advanced prostate cancer management: are all novel antiandrogens the same? - Emre Yekedüz (Prostate International, 2021)
Prostate cancer (PCa) is the most common cancer in men. Androgen receptor axis plays a crucial role in the carcinogenesis of PCa. The mainstay treatment of prostate cancer is blockage of androgen receptor axis but in a vast majority of patient resistance to androgen deprivation therapy is inevitable. After using enzalutamide, the first new generation anti-androgen (AA), two new generation AA drugs were synthesized. New generation anti-androgen drugs are used especially in castration resistance prostate cancer. But recently, there are new publications regarding using new generation anti-androgens in castration sensitive prostate cancer patients. In this review, we will compare structure, mechanisms of effect and clinical outcomes in phase 3 trials of these new generation AA drugs.